Hierarki Kebutuhan Tokoh Utama Dalam Novel Edensor Karya Andrea Hirata - Djumadin , Hawiah (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
This study aims to identify and describe the Hierarchy of Needs for the Main Characters in Andrea Hirata's Edensor Novel. The approach used in this research is descriptive qualitative. The data in this study are in the form of words, phrases, sentences that show the Hierarchy of Needs for the Main Characters in Andrea Hirata's Edensor Novel. The data source is the Edensor Novel by Andrea Hirata. Data collection techniques are: 1) Reading novels. 2) Take notes. Data analysis techniques in this study, namely; (1) data reduction, (2) data codification (3) data classification, (4) data description, (5) data interpretation, (6) data verification. The theory used is Abraham Maslow's theory of Humanistic Psychology. The results of the study indicate that there is a hierarchy of needs from the main character. Starting from the physiological needs, the need for security, the need for belonging and love, the need for esteem, the need for self-actualization.